Development of Interactive Learning Media to Foster the Creativity of Elementary School Students - Atik Nasehatul Khoiriyah; Bambang Subali; Suharto Linuwih (Universitas Negeri Semarang, 2022)
Science learning that takes place in elementary schools is still teacher-centered,it can be seen that the teacher's ability to design learning and the use of learning media is still less interactive and less practical so that learning is monotonous, has not used models or media in science learning. The purpose of the study analyzes the validity, the effectiveness of collaboration of interactive learning media and interactive student woorksheets with problem-based learning models on mastery of concepts and student creativity. This research is development research (Four-D Models) with stages of defining, design, develop and disseminate. Data collection methods are questionnaires, tests and interviews.This research was conducted in grade V SD Negeri 2 Plantaran SouthKaliwungu District, Kendal Regency. The results showed that the development of learning media to foster student creativity was very valid with a percentage of interactive learning media validation score of 98.33%; Analysis of student responses 65.21%. The effectiveness of the product shows that there is an increase in learning outcomes and student creativity increases with good criteria. The benefits of research results make it easier for students to understand the material provided by the teacher so that student learning outcomes increase. The conclusion of this research is that collaboration in the development of interactive learning media and interactive student worksheets with a problem-based learning model can improve learning outcomes and foster the creativity ofelementary school students.